Physicochemical and antibacterial pathogenic characterization of papaya leaf extract liquid soap (Carica papaya L.) - Dewi Handayani; Yesi Hepriyeni; Hermansyah Amir; Sura Menda Ginting; Nurhamidah Nurhamidah (Jurnal Pendidikan Kimia, 2024)
This research aims to identify the physicochemical characteristics and pathogenic antibacterial activity of papaya leaf extract liquid soap (Carica Papaya L.). The sample used was papaya leaf extract whose mass was varied. The data acquisition process was obtained from the results of physicochemical testing of liquid soap formulations and from the results of antibacterial activity tests. This research began by extracting the sample using maceration technique. The extract was then formulated to be the liquid soap formulation 1, 2 and 3 with various masses i.e. three, four and five grams of extract, respectively. The physicochemical test showed that the organoleptic test, pH test, foam height test, specific gravity test, water content test and free alkali test met the SNI physical quality standards for liquid soap and the antibacterial activity test carried out on S. aureus and E. coli bacteria was obtained for S. aureus bacteria. formulations 1, 2 and 3 produce resistance of 2.06 mm, 2.21 mm and 2.46 mm respectively. Meanwhile, for E. coli bacteria, the inhibitory power produced by formulations 1, 2 and 3 was 2.84 mm, 3.41 mm and 3.71 mm, respectively. Based on the results of this research, it can be concluded that the liquid soap formulation from papaya leaf extract meets the physical standards for liquid soap quality according to SNI and has antibacterial activity.